Isolation and characterization of microsatellite loci for Cornus sanguinea (Cornaceae)1. (2nd September 2013) - Wadl, Phillip A.; Hatmaker, E. Anne; Fussi, Barbara; Scheffler, Brian E.; Trigiano, Robert N.
Abstract : Premise of the study: To facilitate genetic and conservation research of Cornus sanguinea, microsatellite loci were isolated and 29 individuals from 11 German populations were genotyped. Methods and Results: Sixteen microsatellite loci were characterized from an enriched small insert genomic library. The number of alleles detected ranged from five to 11 per locus, observed heterozygosity ranged from 0.00 to 1.00, expected heterozygosity ranged from 0.65 to 0.90, and polymorphic information content ranged from 0.59 to 0.88. Conclusions: The markers described in the study will allow further investigation of population dynamics and the degree of clonal reproduction within populations of C. sanguinea .